2013
DOI: 10.1590/s1807-25772013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral health in patients with mental disorders attended at the clinic of oral diagnosis of a public university

Abstract: INTRODUCTION: Many people suffering from mental disorders fail to adequately perform self-care, especially in relation to personal hygiene and in particular to oral hygiene. For these individuals, the prevention and ongoing clinical monitoring are essential. OBJECTIVE: To investigate the oral diseases that most affect patients with mental disorders attended in the Dental College of the Federal University of Piauí (UFPI). METHODOLOGY: Patients treated during the 2nd half of 2011 and 1st half of 2012 were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
1
0
10
Order By: Relevance
“…Em Azrina et al 26 , apenas sete dos 114 participantes utilizavam fio dental, assim como Sacchetto et al 1 verificaram que 70% dos pacientes referiram não possuir este hábito. O acesso do fio ao espaço interproximal pode ser facilitado com o uso do porta-fio dental, que consiste em duas hastes nas quais o fio é fixado.…”
unclassified
“…Em Azrina et al 26 , apenas sete dos 114 participantes utilizavam fio dental, assim como Sacchetto et al 1 verificaram que 70% dos pacientes referiram não possuir este hábito. O acesso do fio ao espaço interproximal pode ser facilitado com o uso do porta-fio dental, que consiste em duas hastes nas quais o fio é fixado.…”
unclassified
“…Podemos constatar, a partir dos resultados apresentados, que a maioria dos entrevistados era do sexo feminino, a média de idade foi de 44,7 anos e a escolaridade mais prevalente foi Ensino Fundamental Incompleto, sendo caracterizada como baixa. Ao realizar um trabalho 7 com pacientes portadores de transtorno mental em Teresina/PI, Sacchetto et al 7 (2013) constataram que o grau de escolaridade também ISSN 1983-5183 foi baixo, sendo que 40% dos participantes possuíam ensino médio completo, 37% tinham menos que 4 anos de estudo e 15% eram analfabetos. No CAPS II de Criciúma/SC os resultados apresentaram-se similares a outro estudo 8 realizado na cidade de Butantã/SP, que também avaliou o impacto da saúde bucal na qualidade de vida de frequentadores do CAPS II -Butantã/SP, onde 46% tinham ensino fundamental incompleto, 24% ensino médio completo, 4% ensino médio incompleto, 20% possuíam ensino fundamental completo e apenas 6% haviam se formado no ensino superior.…”
Section: Discussionunclassified
“…Indivíduos com desordens mentais apresentam maiores chances de comprometimento da sua saúde bucal 6,7,8,9 . Devido a algumas limitações, muitos deles estão mais susceptíveis a doenças de ordem dentobucal, tanto pelo uso de medicamentos, que geralmente acarretam xerostomia, quanto pelo sistema emocional que geralmente se encontra abalado.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Studies of with people with SHCN have shown that these individuals have a higher risk for certain oral diseases, such as dental caries and gingivitis [16,25,30], which may be due to their general/ medical condition, motor difficulties, use of drugs that reduce salivary flow, and delay in receiving preventive guidance regarding oral health [25].…”
Section: Introductionmentioning
confidence: 99%